Strategi Komunikasi Pemasaran Terpadu pada Pada Promosi Film Nanti Kita Cerita Tentang Hari Ini - Syifa Mutiara; Tantan Hermansyah; Nasichah Nasichah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Film has developed into a medium of expression that has commercial value. Film also has the function of mass media, namely to entertain audiences or viewers. Behind the signs of progress and the current national film industry, there are still gaps and ups and downs in its growth. There are a number of problems that are still found in the film production process. To overcome this problem in the production of a film, a promotional strategy is needed to disseminate information widely regarding the publication of films that have been produced. The purpose of this study is to find out the integrated marketing communication strategy in the film "Later We Tell About Today". The results found were an integrated marketing communication strategy used by the production team in the film Nanti Kita Cerita tentang Hari Ini through four ways: advertising, promotion, public relations and personal selling. The advertising strategy for films is carried out though the use of Instagram and YouTube media in the form of photos and videos posted on the official social media of NKCTHI and Visinema Pictures. The photos and videos posted include: updates on the number of viewers, movie trailers, short movie clips, behind the scenes videos, audience reviews and so on. The promotion strategy is holding quizzes with prizes, giveaways, and ticket discounts for the audience. The public relations strategy is to hold media visits with various local and national radio mass media, and hold press conferences in collaboration with print and online media prior to the official showing of the film. Personal selling strategy, namely by holding meet and great events, with the spectators, as well as fans or fans of the cast of NKCTHI.